International Proficiency Study of a Consensus L1 PCR Assay for the Detection and Typing of Human Papillomavirus DNA: Evaluation of Accuracy and Intralaboratory and Interlaboratory Agreement - Kornegay, Janet R. (American Society for Microbiology, 2003)
The PGMY L1 consensus primer pair combined with the line blot assay allows the detection of 27 genital human papillomavirus (HPV) genotypes. We conducted an intralaboratory and interlaboratory agreement study to assess the accuracy and reproducibility of PCR for HPV DNA detection and typing using the PGMY primers and typing amplicons with the line blot (PGMY-LB) assay. A test panel of 109 samples consisting of 29 HPV-negative (10 buffer controls and 19 genital samples) and 80 HPV-positive samples (60 genital samples and 20 controls with small or large amounts of HPV DNA plasmids) were tested blindly in triplicate by three laboratories. Intralaboratory agreement ranged from 86 to 98% for HPV DNA detection. PGMY-LB assay results for samples with a low copy number of HPV DNA were less reproducible. The rate of intralaboratory agreement excluding negative results for HPV typing ranged from 78 to 96%. Interlaboratory reliability for HPV DNA positivity and HPV typing was very good, with levels of agreement of >95% and kappa values of >0.87. Again, low-copy-number samples were more prone to generating discrepant results. The accuracy varied from 91 to 100% for HPV DNA positivity and from 90 to 100% for HPV typing. HPV testing can thus be accomplished reliably with PCR by using a standardized written protocol and quality-controlled reagents. The use of validated HPV DNA detection and typing assays demonstrating excellent interlaboratory agreement will allow investigators to better compare results between epidemiological studies.